ADMINISTRATIVE INTERFERENCE OF THE EUROPEAN SUPERVISORS IN THE EU FINANCIAL MARKET - Michór, Andrzej (Ekonomia i Prawo. Economics and Law, 2011)
Financial stability is a precondition for the real economy to provide jobs, credit and growth. The financial crisis exposed important shortcomings in financial supervision, both in particular cases and in relation to the financial system as a whole. The problem is that nationally based supervisory models have lagged behind financial globalisation and the integrated and interconnected reality of European financial markets, in which many financial institutions operate across borders. The crisis exposed shortcomings in the areas of cooperation, coordination, consistent application of Union law and trust between national supervisors. The article deals with the issue of new regulations on supervision over financial markets of the EU as regards interference of administrative law into the financial market of the European Union. In particular author considers the premises and nature of powers conferred on the new supervision authorities and draws attention to inconsistencies of the provisions of national law with new UE regulations.